EFEKTIVITAS MODEL EXAMPLE NON EXAMPLE TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI EKOSISTEM - Islamiah, Syarifah Rabiatul; Hardi, Basuki; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to find out students?s activity and learning achievement in ecosystem. The research form is quasi experimental design with Non equivalent control group design design. The research sample is class X F (experimental class) and class X J (control class), intact group sampling technique. Instruments used in the form of activity observation sheets and multiple choice test amounted to 20 questions. The average percentage of students' activity in the experimental class is 97,5% include active category, while in control class is 58,35% category is quite active. The average post-test result of the students in the experimental class is 16.90, whereas in the control class is 14.50 and obtained - (-2,87> 1,96), it means there are significant differences in student learning outcomes taught using model learning Example Non Example and taught by direct instruction model. Effect Size value obtained by 0.99 with high category and contributed 33.89%. Against student learning outcomes on the material ecosystem. Keywords : Students activity, learning achievement, model example non example, ecosystem lesson.